1997
DOI: 10.1002/crat.2170320103
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Crystalline Layers of High Temperature Superconductors: Characterization and Application

Abstract: Outline Introduction HTS IntroductionCrystalline materials are prepared as bulk single crystals, epitaxial layers, powders, and fibers for basic research and for applications in demonstrations and devices. The materials spectrum for basic research is extremely broad and the demands on size and quality are relatively modest. Contrary, crystalline materials for technical applications have to be tailored carefully regarding crystal quality, size, and not at last price. Unfortunately, there is no ideal growth meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The REBCO single-crystalline film grown by the liquid phase epitaxy has been among the most important materials for electronic devices and coated conductors, , due to their attractive properties. Because of the complicated atomic structures and the anisotropy of REBCO materials, films with different orientations exhibit distinct properties and behaviors.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The REBCO single-crystalline film grown by the liquid phase epitaxy has been among the most important materials for electronic devices and coated conductors, , due to their attractive properties. Because of the complicated atomic structures and the anisotropy of REBCO materials, films with different orientations exhibit distinct properties and behaviors.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…The second group has a large lattice misfit with REBCO, such as MgO, SrTiO 3 , LaAlO 3 , NiO, Ag and yttrium stabilized ZrO 2 (YSZ), for which REBCO LPE growth essentially needs the thin-film-seed layer or even buffer material. [5][6][7][8][13][14] It was reported that the height of the surface-wetting front (h) is approximately linearly related to the square root of the dipping time (t) as follows: 15 [7.1] where α is the coefficient of the wettability of solution to the substrate materials. From Table 7.1, we can see that the MgO material has the lowest α value, and the Ba-Cu-O (BCO) liquid allows a low Mg solubility (about 0.4 at %).…”
Section: Mode Of Lpe Growthmentioning
confidence: 99%
“…REBa 2 Cu 3 O y (REBCO or RE123) thick films and coated conductors may be grown epitaxially directly on some gallate substrate materials, such as NdGaO 3 , LaGaO 3 and LaSrGaO 4 [1][2][3][4], while for most other substrate materials, e.g., LaAlO 3 , SrTiO 3 , MgO, NiO, Ag and yttrium stabilized ZrO 2 (YSZ), a thin film seed layer is indispensable [5][6][7][8][9][10]. Asaoka et al found that the RE123 phase can be formed around the RE 2 BaCuO 5 (RE211) phase, and Sandiumenge showed some SAD patterns that indicated parallelism between crystallographic directions of the Y211 precipitate and the Y123 matrix, i.e.…”
Section: Introductionmentioning
confidence: 99%